Functional group tolerance in BTB-based metal-organic frameworks (BTB - benzene-1,3,5-tribenzoate) - Helten, Stella; Sahoo, Basudev; Mueller, Philipp; Janssen-Mueller, Daniel; Klein, Nicole; Gruenker, Ronny; Bon, Volodymyr; Glorius, Frank; Kaskel, Stefan; Senkovska, Irena (Microporous and Mesoporous Materials, 2015)
The effect of different substituents on the structural tolerance of benzene-1,3,5-tribenzoate (BTB) based MOFs was studied. For this purpose, three new BTB derivatives ((NH2)3-BTB, tri((tert-butoxycarbonyl)-amino)-BTB; tri((S)-2-acetoxy-2-phenylacetamido)-BTB) were synthesized and utilized in MOF synthesis using synthetic conditions established for eight known MOFs. Three new isoreticular compounds (NH2-DUT-6, NHBoc-DUT-25, mand-DUT-25) could be identified. Furthermore, two compounds with network topologies differing from the parent compound comprising NHBoc-BTB and Cu-paddlewheels as nodes were found: Cu2(H2O)2(H(NHBoc)-BTB)2 (1), a dense structure containing layers with Sql topology, and Cu3(H2O)(NHBoc-BTB)2(bipy) (bipy - 4,4′-bipyridine, DUT-109), with crosslinked Iab-network. The porosity of DUT-109 was proven by liquid phase adsorption of ethyl cinnamate from n-heptane. In general, a significant influence of the BTB substituent on the framework formation could be demonstrated.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Crystallization; Functional BTB derivatives; IRMOFs; Metal-organic frameworks